Positive plate, battery and electric equipment
By controlling the manganese-iron-ferromanganese ratio, acidity growth rate and peak strength ratio in the positive electrode sheet, the boron-containing CEI film is formed, which solves the problems of manganese ion dissolution and active lithium consumption, and improves the circulation performance and life of the lithium-ion battery.
Patent Information
- Application Number
- CN202411888965.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The cycleability and lifespan of existing lithium-ion batteries are mainly due to the problems of manganese ion dissolution and active lithium consumption.
By controlling the manganese-iron-ferromanium- and acidity growth rate and peak-strength ratio in the positive electrode sheet, the boron-containing stable positive electrode solid electrolyte interface film (CEI film) is formed to prevent manganese ions from dissolution and reduce active lithium consumption.
It effectively improves the cycling performance and life of the battery, reduces manganese ion dissolution and active lithium consumption, and improves the stability of the battery.
Smart Images

Figure CN119601591A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention with a filing date of October 18, 2024, an invention name of “A positive electrode sheet, a battery and electrical equipment” and an application number of 202411456396.0. Technical Field
[0002] The invention belongs to the technical field of batteries, and in particular relates to a positive electrode sheet, a battery and an electrical device. Background Art
[0003] As the technology industry continues to develop, the importance of lithium-ion battery storage capacity has gradually been recognized; however, the problem of transition metal dissolution occurs frequently in almost all layered transition metal oxide positive electrodes.
[0004] For the LMFP system, the dissolution of Mn ions affects the stability of the positive electrode material itself, and at the same time, its deposition at the negative electrode leads to the loss of active lithium. The damage of the negative electrode SEI film gradually intensifies, which is an important reason for the life decay.
[0005] Therefore, how to improve the cyclability of batteries and increase their lifespan is an urgent problem that needs to be solved. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a positive electrode sheet, a battery and an electrical device, which forms a stable positive electrode solid electrolyte interface film (CEI film) containing boron (B) on the surface of the positive electrode sheet by controlling the manganese-iron ratio, the acidity growth rate and the peak intensity ratio when etching to a certain depth, thereby preventing the dissolution of manganese ions, reducing the consumption of active lithium and improving the cycle.
[0007] The present invention provides a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material, the positive electrode active material comprises lithium manganese iron phosphate particles;
[0008] The molar ratio of manganese element to iron element in the positive electrode active material is a; the acidity growth rate of the positive electrode sheet is h, unit: %;
[0009] k=b / L, where L is the depth of the positive electrode sheet etched by XPS, which is 10nm; at 10nm, k is the peak intensity ratio of the B1s peak at the binding energy of 188~192eV in the XPS graph when the positive electrode sheet is etched by XPS, and the unit is counts / s / nm; b is the peak intensity of the B1s peak at the binding energy of 188~192eV in the XPS graph when the positive electrode sheet is etched by XPS, and the unit is counts / s;
[0010] The a, k and h satisfy the following relationship:
[0011] a×h / k=8×10 -4 ~10.
[0012] The positive electrode sheet forms a stable CEI film containing B on the surface of the positive electrode sheet by controlling the manganese-iron ratio, acidity growth rate and peak intensity ratio when etching to a certain depth, thereby preventing manganese ions from dissolving, reducing active lithium consumption and improving circulation.
[0013] In a specific implementation manner of the present invention, a×h / k=0.02~3.
[0014] In a specific embodiment of the present invention, 0.1≤a≤9.
[0015] In a specific embodiment of the present invention, 0.4≤a≤2.5.
[0016] In a specific implementation manner of the present invention, 5≤k≤400.
[0017] In a specific implementation manner of the present invention, 9≤k≤108.
[0018] In a specific embodiment of the present invention, the acidity growth rate h is 3-18%.
[0019] In a specific embodiment of the present invention, the acidity growth rate h is 4-16%.
[0020] In a specific embodiment of the present invention, the lithium manganese iron phosphate particles include primary particles, and the particle size of the primary particles ranges from 50 to 170 nm.
[0021] Preferably, the XPS etching depth is 10 nm, and the peak intensity of the B1s peak is F1; the XPS etching depth is 35 nm, and the peak intensity of the B1s peak is F2;
[0022] The difference between F1 and F2 is greater than 0 and less than or equal to 2000.
[0023] The present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0024] The positive electrode sheet is the positive electrode sheet described in the above technical solution.
[0025] In a specific embodiment of the present invention, a boron-containing compound is provided in the electrolyte and / or the positive electrode sheet.
[0026] In a specific embodiment of the present invention, the electrolyte includes a boron-containing compound, and the boron-containing compound is selected from one or more of lithium bis(oxalatoborate), tris(trimethylsilyl)borate, lithium difluorooxalatoborate, lithium tetrafluoroborate, tributyl borate and trimethyl borate.
[0027] The present invention provides an electrical device, comprising the battery described in the above technical solution.
[0028] The present invention uses the battery to prepare electrical equipment. The battery can be used as a power source for the electrical equipment or as an energy storage unit for the electrical equipment, thereby expanding the application range of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the XPS spectrum of the positive electrode sheet prepared in Example 12 of the present invention at an etching depth of 10 nm. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0032] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0034] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0035] The present invention provides a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material, the positive electrode active material comprises lithium manganese iron phosphate particles;
[0036] The molar ratio of manganese element to iron element in the positive electrode active material is a; the acidity growth rate of the positive electrode sheet is h, unit: %;
[0037] k=b / L, where k is the peak intensity ratio of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s / nm; L is the depth of the XPS etching positive electrode sheet, which is 10nm; b is the peak intensity of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s;
[0038] The a, k and h satisfy the following relationship:
[0039] a×h / k=8×10 -4 ~10.
[0040] The positive electrode sheet forms a stable CEI film containing boron (B) on the surface of the positive electrode sheet by controlling the manganese-iron ratio, acidity growth rate and peak intensity ratio when etching to a certain depth, thereby preventing manganese ions from dissolving, reducing active lithium consumption and improving circulation.
[0041] In the present invention, a is the molar ratio of manganese element to iron element;
[0042] In the present invention, the value of a is preferably 0.1≤a≤9. If the Mn content is too high, the transition metal will be seriously dissolved, which will deteriorate the cycle; if it is lower than the above preferred value, the gram capacity will be deteriorated. Specifically, the value of a can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4 .4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.57.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0.
[0043] More preferably, 0.4≤a≤2.5. Within this range, the cycle performance of the battery is better.
[0044] In a specific embodiment of the present invention, the value of a is 0.1, 2.8, 0.5, 2.3, 1.5, 0.4, 2.5, 1.5, 2, 0.4, 0.2, 9, 0.08, or 10.
[0045] In the present invention, k is the peak intensity ratio of the boron element during XPS etching, and its value reflects the content of boron in the surface layer of the positive electrode sheet, which can reflect that the solid electrolyte membrane (CEI membrane) formed on the surface of the positive electrode active material contains a certain amount of boron. K is the peak intensity ratio of the B1s peak at the binding energy of 188-192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, which reflects the content of boron in the surface layer of the positive electrode sheet, and the unit is counts / s / nm; wherein, k=b / L, b is the peak intensity of the B1s peak at the binding energy of 188-192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, and the peak intensity indirectly reflects the content of boron, and the higher the peak intensity, the higher the content of boron at this depth; L is the depth of the positive electrode sheet etched by XPS, and the unit is nm. The role of element B in the surface layer: element B lacks electrons and can combine with anions or anionic groups to form polyanionic groups. The molecular orbital energy level is high and it is easily oxidized. It directly participates in the formation of CEI in the form of anionic groups, thereby protecting the positive electrode and reducing the risk of manganese dissolution in the positive electrode active material.
[0046] In the present invention, the value of k is preferably 5≤k≤400; within the above preferred range, the positive electrode can be protected to avoid transition metal dissolution; at the same time, the impedance increase and the cycle performance attenuation can be avoided. The value of K can be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, 210 , 215, 220, 225, 230, 235, 240, 245, 250, 255, 260, 265, 270, 275, 280, 285, 290, 295, 300, 305, 310, 315, 320, 325, 330, 335, 340, 345, 350, 355, 360, 365, 370, 375, 380, 385, 390, 395, or 400.
[0047] More preferably, 9≤k≤108; the value of k can be 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54 , 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, or 105.
[0048] In specific embodiments of the present invention, the value of k is 400, 5, 108, 12, 45, 95, 9, 380, 43, 90, 7, 125, 100, or 20.
[0049] In the present invention, h is the acidity growth rate, unit: %; the acidity growth rate is the growth rate of hydrogen ion content generated when the positive electrode sheet is immersed in a mixed solution containing lithium perchlorate, due to the side reaction between the positive electrode active material and the electrolyte, electrons are gained and lost, EC borrows electrons during the charge and discharge process of LMFP, and EC itself opens the ring for dehydrogenation. If the acidity growth rate is controlled within a certain range, it can protect the positive electrode sheet, reduce excessive side reactions between the positive electrode sheet and the electrolyte, and ensure the kinetic performance; if the acidity growth rate is too large, the side reactions between lithium manganese iron phosphate and the electrolyte will increase, and the cycle will deteriorate; if the acidity growth rate is too small, the solid phase diffusion of lithium ions will increase, and the kinetic performance will deteriorate. Therefore, the acidity growth rate h is preferably 3~18%, and more preferably 4~16%. The acidity growth rate is related to various factors, such as the diameter of the primary particle size, the thickness of the carbon layer of the positive electrode active material, and the amount of conductive agent in the positive electrode sheet.
[0050] In the present invention, the specific value of h can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, and 18%.
[0051] In the specific embodiments of the present invention, the acidity growth rate h is specifically 3.2, 17.5, 4.5, 15.5, 7, 4.2, 16, 15, 16.2, 5, 3, 18, 2, or 19.
[0052] The present invention does not limit the test of acidity growth rate, and those skilled in the art can test it by conventional means; for example, the test can be carried out by the following method:
[0053] 3 pieces of 7×7cm 2 The fully charged positive electrode was immersed in a mixed solution of EC, EMC and lithium perchlorate (the total mixed volume was 20 ml, the mass ratio of EC to EMC was 3:7, and the amount of lithium perchlorate added was 1 mol / L), stored at 60 °C for 2 days, and the H + The solution was stored at 60°C for 3 days and the H + m2 ppm; H + Growth rate, that is, acidity growth rate h, h is (m2-m1) / m1.
[0054] The a, k and h in the present invention satisfy the following relationship: a×h / k=8×10 -4 ~10; in the above relationship, when the upper limit is exceeded, the manganese content is high, and the acidity growth rate is relatively large, if the B content is too low, a dense and stable CEI film cannot be formed at the positive electrode, resulting in more manganese dissolution, large active lithium consumption, and deterioration of the cycle performance; the above relationship exceeds the lower limit, and the boron (B) element content is too high, resulting in increased interface impedance (Rct), SEI film carbon source (Rsei) and diffusion impedance (Ws) during the cycle, resulting in poor cycle performance.
[0055] Specifically, a×h / k=0.0008, 0.0009, 0.001, 0.0015, 0.0020, 0.0025, 0.0030, 0.0035, 0.0040, 0.0045, 0.0050, 0.0060, 0.0070, 0.0080, 0.0090, 0.0095, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0 .14, 0.1436, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2.0, 2.5, 3.0, 3.5, 4, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.
[0056] In the present invention, the preferred range of a×h / k is 0.02-3; within this range, the cycle performance of the battery is more excellent.
[0057] In specific embodiments of the present invention, a×h / k=0.0008, 9.800, 0.0208, 2.9708, 0.2333, 0.0177, 4.4444, 0.0592, 0.7200, 0.0222, 0.0857, 1.2960, 0.0016, or 9.5000.
[0058] The active material in the positive electrode sheet provided by the present invention includes lithium iron manganese phosphate particles; the lithium iron manganese phosphate particles include primary particles, and the average particle size of the primary particles ranges from 50 to 170 nm, or can be 70 to 160 nm. Specifically, the average particle size of the primary particles is 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, or 170 nm. The present invention does not regulate the adjustment method of the primary particle size, and the primary particle size can be selected to regulate the sintering process or the grinding process to change the particle size. In a specific embodiment of the present invention, the particle size of the primary particles is 162nm, 76nm, 151nm, 95nm, 130nm, 155nm, 93nm, 92nm, 41nm, 202nm, 132nm, 200nm or 136nm.
[0059] The positive electrode provided by the present invention uses the XPS method to characterize the intensity of the boron (B) element at a certain etching depth; in the preferred embodiment of the present invention, the peak intensity (F1) of XPS at 10nm and the peak intensity (F2) at 35nm meet the requirements of being greater than 0 and less than or equal to 2000. In the present invention, the B element is mainly in the CEI film layer on the surface of the positive electrode sheet, and the B element mainly participates in the formation of the CEI film layer on the surface of the positive electrode. The B element on the surface helps to stabilize and compact the CEI film layer. If the B element is in the active material layer, the direct contact between the electrode and the electrolyte causes the electrolyte to corrode the positive electrode active material, thereby reducing the cycle stability of the battery; by limiting the peak intensity to be greater than 0 and less than or equal to 2000, B is on the surface, which plays a role in stabilizing CEI, and also avoids the problem of excessive surface B. In the present invention, the difference between F1 and F2 is specifically 45, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, 1550, 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950 or 2000.
[0060] In a specific embodiment of the present invention, the difference between F1 and F2 is 3950, 45, 600, 100, 420, 880, 75, 3550, 400, 750, 50, 980, 890 or 160.
[0061] The present invention forms a uniform CEI film on the positive electrode surface by adjusting the boron content in the positive electrode sheet, inhibiting the dissolution of manganese ions, reducing the consumption of active lithium, and improving the cycle performance of the battery. In the present invention, the boron element is contained in the electrolyte, and, or the positive electrode sheet is provided with a boron-containing compound.
[0062] The boron element is introduced by adding a boron-containing compound to the electrolyte, and the boron-containing compound is selected from one or more of lithium bis(oxalatoborate) (LiBOB), tris(trimethylsilyl)borate (TMSB), lithium difluorooxalatoborate (LIODFB), lithium tetrafluoroborate, tributyl borate and trimethyl borate;
[0063] The boron element is used to set a coating layer on the surface of the positive electrode active material; or a doping substance M is added during the slurry mixing process; the doping substance M is selected from one or more of boric acid, organic borane, borohydride and metal boride; the boron-containing compound in the coating layer is selected from metal boride and / or borate LiMBO3.
[0064] The positive electrode sheet described in the above technical solution of the present invention includes a positive electrode active material; the positive electrode active material includes lithium manganese iron phosphate particles (LMFP);
[0065] In the present invention, the preparation method of the positive electrode active material is not limited, and those skilled in the art can prepare the positive electrode active material according to conventional technical means. Exemplarily, the preparation method of the positive electrode active material includes the following steps:
[0066] The lithium source, manganese source, iron source and phosphorus source required for synthesizing the lithium manganese iron phosphate material are weighed in proportion and added with deionized water, and ground to obtain a lithium manganese iron phosphate precursor slurry;
[0067] Adding the coated carbon source and the lithium iron manganese phosphate precursor slurry to mix evenly, grinding, adjusting the solid content and spray drying to obtain a dry powder;
[0068] The dried powder is sintered in a protective atmosphere and cooled to obtain the positive electrode active material.
[0069] The above scheme cools down to obtain lithium manganese iron phosphate in the form of agglomerates, which have relatively large particle sizes; the lithium manganese iron phosphate in the form of agglomerates is composed of multiple primary particles.
[0070] In some other embodiments, the synthesized positive electrode active material can also be crushed and graded to obtain small particles of lithium manganese iron phosphate, where the small particles of lithium manganese iron phosphate refer to a single particle, or there may be two or three particles connected together and not broken.
[0071] The primary particle size in Table 1 below of the present invention refers to: the primary particle size in the agglomerate; or the small particle size.
[0072] The lithium source in the present invention is selected from at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate and lithium acetate. The manganese source is selected from at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate and manganese acetate; the iron source is selected from at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferrous acetate, ferrous acetate, ferrous carbonate, ferrous carbonate, ferrous trioxide, ferric tetroxide and ferric oxalate; the phosphorus source is selected from at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate and lithium phosphate. The present invention preferably uses ferromanganese phosphate as a manganese source, an iron source and a phosphorus source at the same time; preferably uses ferric phosphate as an iron source and a phosphorus source at the same time.
[0073] In the preparation of lithium manganese iron phosphate particles, the present invention can also be doped with other elements as needed, such as vanadium, tungsten, titanium, magnesium, etc.; to provide the above elements, the vanadium source used is selected from vanadium pentoxide, etc., the tungsten source is selected from ammonium metatungstate, etc., the titanium source is selected from titanium oxide, etc., and the magnesium source is selected from magnesium carbonate, etc. The content of other doped elements in the present invention is based on the total molar ratio of manganese and iron, preferably 1000~5000ppm. The structural formula of the lithium manganese iron phosphate particles described in the present invention is: LiMn x Fe y M z n PO4, wherein x is greater than 0 and less than 1; y is greater than 0 and less than 1; z is greater than or equal to 0 and less than 1; n refers to the valence of the doping element; 2(x+y)+n×z=2.
[0074] In the present invention, the carbon source content is based on the total amount of solid matter in the lithium iron manganese phosphate precursor slurry, preferably 5-35%, and the carbon source content is specifically 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%.
[0075] In specific embodiments of the present invention, the carbon source content is 30%, 12%, 25%, 17%, 20%, 28%, 15%, 16%, 5%, 20%, 28%, 12%, 35%, or 10%.
[0076] The present invention mixes a lithium source, a manganese source, an iron source and a phosphorus source to obtain a manganese iron lithium slurry, which is then mixed with a coated carbon source. The coated carbon source is selected from at least one of glucose, polyethylene glycol, acetylene black, glycine, starch, acetylene black, sucrose, phenolic resin and ascorbic acid. The solvent used in the present invention is water and / or ethanol. The grinding method in the present invention can be ball milling.
[0077] The present invention sintered the precursor by using a gradient sintering method; the gradient sintering includes:
[0078] The temperature is raised to 150-630°C at a heating rate of 4-6°C / min and pre-fired for 280-330min. The temperature is then raised to 300-950°C at a heating rate of 9-11°C / min and calcined for 700-750min.
[0079] The present invention preferably adopts a natural cooling method to obtain lithium manganese iron phosphate particles.
[0080] The positive electrode active material in the present invention preferably also includes lithium iron phosphate (LFP), and the specific structural formula of lithium iron phosphate is LiFePO4, that is, a composite of lithium iron manganese phosphate particles and lithium iron phosphate. The mass ratio of lithium iron manganese phosphate particles to lithium iron phosphate in the present invention is 0.14 to 56. In a specific embodiment of the present application, the mass ratio of LMFP to LFP is 0.14, 56.0, 0.81, 13.14, 4, 0.61, 20, 4, 8, 0.61, 0.29, 0.11 or 22.2.
[0081] The positive electrode sheet provided by the present invention includes not only a positive electrode active material, but also a conductive agent and a binder. The mass ratio of the positive electrode active material, the conductive agent and the binder in the present invention is 96: (0.1-3): (3.9-1).
[0082] The conductive agent included in the positive electrode sheet provided by the present invention only needs to have suitable electronic conductivity and not cause adverse chemical changes in the battery, and the type of the conductive agent is not particularly limited in the present invention. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black and graphene.
[0083] The binder included in the positive electrode sheet provided by the present invention is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) and sodium alginate.
[0084] The positive electrode sheet provided by the present invention also includes a positive electrode current collector. The present invention has no particular restrictions on the positive electrode current collector, as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0085] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent such as NMP (N-methylpyrrolidone) to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0086] The present invention also provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0087] The positive electrode sheet is the positive electrode sheet described in any one of the above technical solutions.
[0088] The battery provided by the present invention has excellent cycle performance by adopting the positive electrode sheet.
[0089] The present invention can introduce boron into the prepared battery by providing a boron-containing compound in the electrolyte and / or the positive electrode sheet. The boron-containing compound in the electrolyte of the present invention is selected from one or more of lithium bis(oxalatoborate) (LiBOB), tris(trimethylsilyl)borate (TMSB), lithium difluorooxalatoborate (LIODFB), lithium tetrafluoroborate, tributyl borate and trimethyl borate.
[0090] In the present invention, the boron element is introduced into the positive electrode sheet, and a coating layer can be provided on the surface of the positive electrode active material; or a doping substance M can be added during the slurry mixing process. The boron-containing compound in the coating layer is selected from metal borides and / or borates LiMBO3; the doping substance M is selected from one or more of boric acid, organic borane, borohydride and metal boride.
[0091] The negative electrode sheet in the present invention comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material.
[0092] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0093] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector; for example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0094] The present invention provides an electrical device, comprising the battery described in the above technical solution.
[0095] The battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0096] In order to further illustrate the present invention, a positive electrode sheet, a battery and an electrical device provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0097] Example 1
[0098] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is as follows: lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are weighed respectively, deionized water is added, mixed, and ball-milled to obtain a lithium iron manganese phosphate precursor slurry, and then 30% glucose with a mass fraction is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball-milled for 20 hours, and then the solid content is adjusted and spray-dried to obtain a dry powder; the dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5°C / min to 600°C for pre-calcination for 300min, and then the temperature is increased to 800°C at a heating rate of 10°C / min, calcined for 720min, and a solid powder is obtained after natural cooling; the solid powder is then crushed, and after crushing for 8h, it is screened to obtain the target material LiMn 0.75 Fe 0.25 PO4 positive electrode material.
[0099] (2) Preparation of positive electrode sheet: The lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 1:10 as the main material, and the compounding ratio of LMFP and LFP is 0.14. The main material, conductive agent SP, and binder polyvinylidene fluoride (PVDF) are mixed evenly in NMP according to the mass ratio of 96:3:1. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0100] (3) The electrolyte has a solvent system of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7 wt%, 1.15M LiPF6 as the lithium salt, and 3300ppm of lithium bis(oxalato)borate (LiBOB) containing B element additives, 1% vinylene carbonate (VC), and 1% methylene disulfonate (MMDS) as film-forming additives.
[0101] (4) Preparation of negative electrode sheet
[0102] The negative electrode active material (artificial graphite), conductive agent (SP), and binder (carboxymethyl cellulose, CMC) are mixed in a mass ratio of 96.4:1:2.6 and dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil). The negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven for drying at 100°C, and then rolled, cut, and baked to obtain a negative electrode sheet.
[0103] (5) Preparation of diaphragm
[0104] Polyethylene (PE) diaphragm is used.
[0105] (6) Preparation of batteries
[0106] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0107] Example 2
[0108] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is as follows: lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are weighed respectively, deionized water is added, mixed, and ball-milled to obtain a lithium iron manganese phosphate precursor slurry, and then 12% of glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball-milled for 20 hours, and then the solid content is adjusted and spray-dried to obtain a dry powder; the dry powder is then placed in a tubular furnace and calcined, the heating rate is 5°C / min to 200°C for pre-calcination for 300min, and then the temperature is increased to 400°C at a heating rate of 10°C / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0109] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 2.8 as the main material, and the compounding ratio of LMFP and LFP is 56.0. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:0.2:3.8, and finally trimethyl borate containing 45ppm of B element is added to continue slurry mixing. Subsequently, the mixed positive electrode slurry is mixed according to the surface density of 400g / m 2The film is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain a positive electrode sheet, which is then slit; then rolled and cut to obtain a positive electrode sheet.
[0110] (3) The electrolyte has a solvent system of EC:EMC=3:7 wt%, 1.15M LiPF6 as lithium salt, and 1% VC and 1% MMDS as film-forming additives.
[0111] (4) Preparation of negative electrode sheet: same as in Example 1.
[0112] (5) Preparation of diaphragm: same as in Example 1.
[0113] (6) Preparation of battery: same as in Example 1.
[0114] Example 3
[0115] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball-milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 25% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball-milled for 20 hours. After that, the solid content is adjusted and spray-dried to obtain a dry powder. Then, the dry powder is mixed evenly with boric acid (B content 900ppm) and placed in a tubular furnace for calcination. The heating rate is 5℃ / min to 400℃ for pre-calcination for 300 min, and then the temperature is increased to 750℃ at a heating rate of 10℃ / min, calcined for 720min, and solid powder is obtained after natural cooling. The solid powder is then crushed for 6 hours to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0116] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.5 as the main material, and the compounding ratio of LMFP and LFP is 0.81. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:2.5:1.5. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0117] (3) The electrolyte is the same as that in Example 2.
[0118] (4) Preparation of negative electrode sheet: same as in Example 1.
[0119] (5) Preparation of diaphragm: same as in Example 1.
[0120] (6) Preparation of battery: same as in Example 1.
[0121] Example 4
[0122] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is 5. Lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are weighed respectively, deionized water is added, mixed, and ball milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 17% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 15 hours, and then the solid content is adjusted and spray dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 300℃ for pre-calcination for 300 min, and then the temperature is increased to 500℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0123] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe0 .25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 2.3 as the main material, and the compounding ratio of LMFP and LFP is 13.14. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:0.8:3.2. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0124] (3) The electrolyte is different from that in Example 1: an additive LiBOB containing 130 ppm of B element is selected.
[0125] (4) Preparation of negative electrode sheet: same as in Example 1.
[0126] (5) Preparation of diaphragm: same as in Example 1.
[0127] (6) Preparation of battery: same as in Example 1.
[0128] Example 5
[0129] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 20% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball milled for 20 hours. After that, the solid content is adjusted and spray dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 400℃ for pre-calcination for 300 min, and then the temperature is increased to 600℃ at a heating rate of 10℃ / min, calcined for 720min, and solid powder is obtained after natural cooling. The solid powder is crushed, and after 12 hours, LiMn 0.75 Fe 0.25 PO4 material.
[0130] (2) Preparation of positive electrode:
[0131] Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 1.5 as the main material, and the compounding ratio of LMFP and LFP is 4. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:1:3. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The film is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain a positive electrode sheet, which is then slit; then rolled and cut to obtain a positive electrode sheet.
[0132] (3) Preparation of negative electrode sheet: same as in Example 1.
[0133] (4) Preparation of electrolyte: Compared with Example 1, a LIODFB additive containing 380 ppm of B element was selected.
[0134] (5) Preparation of isolation membrane: PP is used as the isolation membrane.
[0135] (6) Preparation of battery: same as in Example 1.
[0136] Example 6
[0137] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry, and then 28% glucose is weighed and mixed with the lithium iron manganese phosphate precursor slurry, ball milled for 20 hours, and then the solid content is adjusted and spray dried to obtain dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 400℃ for pre-calcination for 300 min, and then the temperature is increased to 800℃ at a heating rate of 10℃ / min, calcined for 720min, and solid powder is obtained after natural cooling, and then the solid powder is crushed for 6h to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0138] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.4 as the main material, and the compounding ratio of LMFP and LFP is 0.61. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:3:1. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0139] (3) Compared with the embodiment, the electrolyte contains an additive LIODFB containing 805 ppm of boron.
[0140] (4) Preparation of negative electrode sheet: same as in Example 1.
[0141] (5) Preparation of diaphragm: same as in Example 1.
[0142] (6) Preparation of battery: same as in Example 1.
[0143] Embodiment 7:
[0144] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry. Then, 15% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball milled for 22 hours. After that, the solid content is adjusted and spray dried to obtain dry powder. Then, the dry powder is placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 250℃ for pre-calcination for 300 min, and then the temperature is increased to 450℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0145] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 2.5 as the main material, and the compounding ratio of LMFP and LFP is 20. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:0.3:3.7. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0146] (3) Compared with Example 1, the electrolyte used was an additive trimethyl borate containing 80 ppm of B element.
[0147] (4) Preparation of negative electrode sheet: same as in Example 1.
[0148] (5) Preparation of diaphragm: same as in Example 1.
[0149] (6) Preparation of battery: same as in Example 1.
[0150] Embodiment 8:
[0151] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry, and then 20% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 20 hours, and then the solid content is adjusted and spray dried to obtain dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 400℃ for pre-calcination for 300 min, and then the temperature is increased to 480℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0152] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 1.5 as the main material, and the compounding ratio of LMFP and LFP is 4. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:1:3. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0153] (3) Preparation of negative electrode sheet: same as in Example 1.
[0154] (4) Compared with Example 1, the electrolyte contains tributyl borate additive containing 3210 ppm of B element.
[0155] (5) Preparation of diaphragm: same as in Example 1.
[0156] (6) Preparation of battery: same as in Example 1.
[0157] Embodiment 9:
[0158] 1) Preparation of LMFP positive electrode material: According to LiMn 0.75 Fe 0.25The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is 5. Lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are weighed respectively, deionized water is added, mixed, and ball milled to obtain lithium iron manganese phosphate precursor slurry, and then 20% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 30 hours, and then the solid content is adjusted and spray dried to obtain dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 150℃ for pre-calcination for 300min, and then the temperature is increased to 300℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0159] 2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 2 as the main material, and the compounding ratio of LMFP and LFP is 8. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:1.5:2.5. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0160] 3) Preparation of negative electrode sheet: same as in Example 1.
[0161] 4) Compared with Example 1, the electrolyte contains trimethyl borate additive containing 350 ppm of B element.
[0162] Embodiment 10:
[0163] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is as follows: lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are weighed respectively, deionized water is added, mixed, and ball milled to obtain a lithium iron manganese phosphate precursor slurry, and then 20% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 20 hours, and then the solid content is adjusted and spray dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 650℃ for pre-calcination for 300 min, and then the temperature is increased to 900℃ at a heating rate of 10℃ / min, calcined for 720min, and a solid powder is obtained after natural cooling, and then the solid powder is crushed for 9h to obtain LiMn0.75 Fe 0.25 PO4 Materials
[0164] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.4 as the main material, and the compounding ratio of LMFP and LFP is 0.61. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:1.5:2.5. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0165] (3) Preparation of negative electrode sheet: same as in Example 1.
[0166] (4) Compared with Example 1, the electrolyte contains trimethyl borate additive containing 760 ppm of B element.
[0167] (5) Preparation of diaphragm: same as in Example 1.
[0168] (6) Preparation of battery: same as in Example 1.
[0169] Embodiment 11:
[0170] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 28% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball milled for 20 hours. After that, the solid content is adjusted and spray dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 400℃ for pre-calcination for 300min, and then the temperature is increased to 600℃ at a heating rate of 10℃ / min, calcined for 720min, and solid powder is obtained after natural cooling, which is crushed for 10h to obtain LiMn 0.75 Fe 0.25 PO4 material.
[0171] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.2 as the main material, and the compounding ratio of LMFP and LFP is 0.29. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:3:1. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0172] (3) Preparation of negative electrode sheet: same as in Example 1.
[0173] (4) Compared with Example 1, the electrolyte used was a TMSB additive containing 70 ppm of B element.
[0174] (5) Preparation of diaphragm: same as in Example 1.
[0175] (6) Preparation of battery: same as in Example 1.
[0176] Embodiment 12:
[0177] (1) Lithium iron manganese phosphate (LiMn 0.9 Fe 0.1 PO4) positive electrode material: LiMn 0.9 Fe 0.1 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, deionized water is added, mixed, and ball-milled to obtain a lithium iron manganese phosphate precursor slurry, and then 12% of glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball-milled for 20 hours, and then the solid content is adjusted and spray-dried to obtain a dry powder; the dry powder is then placed in a tubular furnace and calcined, and the heating rate is 5°C / min to 400°C for pre-calcination for 300 min, and then the temperature is increased to 600°C at a heating rate of 10°C / min, calcined for 720 min, and the solid powder is obtained after natural cooling. After 14 hours of crushing and screening, the primary particle size shown in Table 1 is obtained;
[0178] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.9 Fe 0.1 PO4) and the conductive agent SP and the binder were mixed in NMP at a mass ratio of 96:1:3. Then, the mixed positive electrode slurry was mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0179] (3) Preparation of negative electrode sheet: same as in Example 1.
[0180] (4) Compared with Example 1, the electrolyte used was a TMSB additive containing 980 ppm of B element.
[0181] (5) Preparation of diaphragm: same as in Example 1.
[0182] (6) Preparation of battery: same as in Example 1.
[0183] Figure 1 This is the XPS spectrum of the positive electrode sheet prepared in Example 12 of the present invention at an etching depth of 10 nm; Figure 1 It can be seen that the peak appearing in the XPS spectrum represents the peak of the B element, among which the peak value represents the peak intensity of the B element of the positive electrode sheet at the etching position of 10nm, which is about 1250 counts / s.
[0184] Embodiment 13:
[0185] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry, and then 35% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 20 hours, and then the solid content is adjusted and spray dried to obtain dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 650℃ for pre-calcination for 300 min, and then the temperature is increased to 900℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material. Then LiMn 0.75 Fe 0.25 The PO4 material was crushed and ground, and after 8 h of crushing and screening, the primary particle size was obtained as shown in Table 1;
[0186] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.08 as the main material, and the compounding ratio of LMFP and LFP is 0.11. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:3:1. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0187] (3) Preparation of negative electrode sheet: same as in Example 1.
[0188] (4) Compared with Example 1, the electrolyte used a LiBOB additive containing 850 ppm of B element.
[0189] (5) Preparation of diaphragm: same as in Example 1.
[0190] (6) Preparation of battery: same as in Example 1.
[0191] Embodiment 14:
[0192] (1) Lithium iron manganese phosphate (LiMn 0.95 Fe 0.05 PO4) positive electrode material: LiMn 0.95 Fe 0.05 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed. Lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate are added, deionized water is added, mixed, and ball milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 10% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 25 hours, and then the solid content is adjusted and spray dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 200℃ for pre-calcination for 300 min, and then the temperature is increased to 450℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.95 Fe 0.05 PO4 material.
[0193] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.95 Fe 0.05 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 10 as the main material, and the compounding ratio of LMFP and LFP is 22.2. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:0.1:3.9. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0194] (3) Preparation of negative electrode sheet: same as in Example 1.
[0195] (4) Compared with Example 1, the electrolyte used a LiBOB additive containing 190 ppm of B element.
[0196] (5) Preparation of diaphragm: same as in Example 1.
[0197] (6) Preparation of battery: same as in Example 1.
[0198] Comparative Example 1
[0199] (1) Lithium iron manganese phosphate (LiMn 0.9 Fe 0.1 PO4) positive electrode material: LiMn 0.9 Fe 0.1 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry. Then, 10% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball milled for 20 hours. After that, the solid content is adjusted and spray dried to obtain dry powder. Then, the dry powder is placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 100℃ for pre-calcination for 300min, and then the temperature is increased to 300℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.9 Fe 0.01 PO4 material.
[0200] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.9 Fe 0.1 PO4) The positive electrode material, conductive agent SP and binder are mixed evenly in NMP at a mass ratio of 96:1:3. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 Evenly coat the aluminum foil, dry it in a vacuum oven at 100°C to obtain a positive electrode sheet, and then slit it; then roll and cut it to obtain a positive electrode sheet;
[0201] (3) Preparation of negative electrode sheet: same as in Example 1;
[0202] (4) Compared with Example 1, the electrolyte solution contains LiBF4 containing 90 ppm of B element, 1% VC, and 1% MMDS as film-forming additives.
[0203] (5) Preparation of diaphragm: same as in Example 1.
[0204] (6) Preparation of battery: same as in Example 1.
[0205] Comparative Example 2:
[0206] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn0.75 Fe 0.25 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball-milled to obtain a lithium iron manganese phosphate precursor slurry. Then, 40% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball-milled for 20 hours. After that, the solid content is adjusted and spray-dried to obtain a dry powder. The dry powder is then placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 600℃ for pre-calcination for 300 min, and then the temperature is increased to 1000℃ at a heating rate of 10℃ / min, calcined for 720min, and solid powder is obtained after natural cooling; the solid powder is then crushed, and after 3.5 hours of crushing and screening, the primary particle size shown in Table 1 is obtained;
[0207] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 0.1 as the main material, and the compounding ratio of LMFP and LFP is 0.14. The main material, conductive agent SP, and binder are mixed evenly in NMP according to the mass ratio of 96:2.5:1.5. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is evenly coated on aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then slit; then rolled and cut to obtain the positive electrode sheet.
[0208] (3) Preparation of negative electrode sheet: same as in Example 1;
[0209] (4) Compared with Example 1, the electrolyte used is an additive LiBF4 containing 3260 ppm of B element.
[0210] (5) Preparation of diaphragm: same as in Example 1.
[0211] (6) Preparation of battery: same as in Example 1.
[0212] Comparative Example 3:
[0213] (1) Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) positive electrode material: LiMn 0.75 Fe 0.25The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and deionized water is added to mix and ball milled to obtain lithium iron manganese phosphate precursor slurry. Then, 40% glucose by mass is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, and ball milled for 20 hours. After that, the solid content is adjusted and spray dried to obtain dry powder. Then, the dry powder is placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 400℃ for pre-calcination for 300 min, and then the temperature is increased to 600℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.75 Fe 0.25 PO4 material. Then LiMn 0.75 Fe 0.25 The PO4 material was crushed, ground and crushed for 12 hours, and screened to obtain the primary particle size shown in Table 1.
[0214] (2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.75 Fe 0.25 PO4) and lithium iron phosphate (LiFePO4) positive electrode materials are mixed evenly according to the Mn / Fe molar ratio of 1.5 as the main material, and the compounding ratio of LMFP to LFP is 4. After the main material, the conductive agent SP and the binder are mixed evenly in NMP according to the mass ratio of 96:1:3, a part of the slurry is taken out, and 35ppm of LiBF4 is added to form the first slurry, and the remaining part is used as the second slurry;
[0215] The first slurry is evenly coated on the aluminum foil and dried in a vacuum oven at 100°C; the second slurry is coated on the first slurry, dried in a vacuum oven at 100°C, and then slit, rolled and cut to obtain a positive electrode sheet.
[0216] (3) Preparation of negative electrode sheet: same as in Example 1;
[0217] (4) Preparation of diaphragm: same as in Example 1.
[0218] (5) Preparation of battery: same as in Example 1.
[0219] Table 1 Values and relationships of a, k, h, etc. in the positive electrode sheets in the embodiments and comparative examples and battery performance test results
[0220] / a k a×h / k Acidity growth rate h / % F2-F1 Primary particle size / nm (the size of the primary particles in the agglomerate; or the size of the primary particles directly after the agglomerate is broken) 25℃ cycle 400 cycles capacity retention rate / % 400clsDCR growth rate / % Example 1 0.10 400 0.0008 3.20 3950 162 68.2 56.1 Example 2 2.8 5 9.80000 17.50 45 76 65.3 41.9 Example 3 0.5 108 0.0208 4.50 600 151 91.5 36.0 Example 4 2.3 12 2.9708 15.50 100 95 96.4 27.2 Example 5 1.5 45 0.2333 7.00 420 130 94.1 24.3 Example 6 0.4 95 0.0177 4.20 880 155 94.2 40.1 Example 7 2.5 9 4.4444 16.00 75 83 76.0 33.5 Example 8 1.5 380 0.0592 15.00 3550 92 77.4 50.6 Example 9 2.0 43 0.7200 16.20 400 41 72.9 36.1 Example 10 0.4 90 0.0222 5.00 750 202 79.4 39.7 Embodiment 11 0.2 7 0.0857 3.00 50 132 86.3 38.2 Example 12 9.0 125 1.2960 18.00 980 136 90.4 30.3 Example 13 0.08 100 0.0016 2.00 890 200 75.6 60.3 Embodiment 14 10 20 9.5000 19.00 160 82 60.3 45.2 Comparative Example 1 9 10 16.2000 18.00 30 33 45.3 63.0 Comparative Example 2 0.1 398 0.0005 2.00 3950 251 50.4 68.5 Comparative Example 3 1.5 3 12.5000 25.00 -50 128 47.5 71.5
[0221] Table 2 Amounts of raw materials and process conditions used in preparing positive electrode sheets in Examples and Comparative Examples
[0222] / The ratio of manganese to iron in the positive electrode active material LMFP:LFP compound ratio Boron addition amount / ppm Example 1 0.1 0.14 3300 Example 2 2.8 56.0 45 Example 3 0.5 0.81 900 Example 4 2.3 13.14 130 Example 5 1.5 4 380 Example 6 0.4 0.61 805 Example 7 2.5 20 80 Example 8 1.5 4 3210 Example 9 2 8 350 Example 10 0.4 0.61 760 Embodiment 11 0.2 0.29 70 Example 12 9 / (Simple manganese iron lithium) 980 Example 13 0.08 0.11 850 Embodiment 14 10 22.2 190 Comparative Example 1 9 / (Simple manganese iron lithium 90 Comparative Example 2 0.1 0.14 3260 Comparative Example 3 1.5 4 35
[0223] Test: Manganese to Iron Ratio (a) Test Method: ICP
[0224] ① Pretreatment: disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with humidity ≤15%; scrape the positive electrode active material layer on the surface of the current collector, calcine it at 400℃ for 3 hours to remove the conductive agent, binder, surface side reaction products, and residual electrolyte, and wash and dry to obtain the positive electrode active material powder.
[0225] ② Accurately weigh 0.5g of positive electrode active material powder, disperse it in 20ml of water, add 10ml of nitric acid, mix well and heat it. After the positive electrode active material powder is dissolved, dilute the material to 100ml with water to obtain the solution to be tested; perform ICP test on the solution to be tested. Before the test, the standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 before it can be used as a normal standard. Dilute the 1000 mg / L standard solution with deionized water to different concentrations (generally 0, 1 mg / 100mL, 2 mg / 100mL, 3mg / 100mL), select the element detection spectrum wavelength, and set the experimental conditions: according to the characteristics of the sample and the elements to be detected, set the appropriate ICP instrument working conditions: gas flow rate 0.5L / min, power 1150W, select element test Fe wavelength 259.94nm, Mn wavelength 257.61nm. The self-service analysis function of the ICP test software can read the concentration of Fe and Mn elements in the sample.
[0226] Peak Intensity Ratio:
[0227] ① Pretreatment: disassemble the lithium-ion battery, obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%;
[0228] ②XPS etching peak intensity ratio (k):
[0229] The electrode to be tested is subjected to XPS etching analysis, and the peak intensity b of the B1s peak at the binding energy position of 188-192 eV in the XPS graph is obtained. Specifically, the etching depth L can be selected to be 10 nm.
[0230] Where, k = b / L;
[0231] The sample is fixed in an appropriate position, such as on the conductive tape of a copper sheet, and then sent to the analysis chamber through the fast sample chamber, using a 120W monochromatic Al Kα X-ray source; the energy resolution is less than or equal to 0.48 eV; the test beam spot is 400 microns, and the instrument automatically supplements the test energy range according to the element to be tested; etching conditions: Ar ions are used for etching, and the etching depth is controlled by adjusting the etching rate or etching time. In the present invention, the etching depth is 10nm (or 35nm). After the test is completed, the instrument will automatically give the test results, and the peak intensity b can be obtained. Combined with the etching depth L, b / L, the peak intensity ratio k is obtained.
[0232] Acidity growth rate:
[0233] Disassemble the fully charged battery (discharge the battery at 0.33C to the lower limit voltage of 2.5V, then charge it at 0.33C constant current to the upper limit voltage of 4.25V, and charge it at constant voltage until the current is less than or equal to 0.05C) to obtain the positive electrode sheet in the fully charged state. The electrode sheet is soaked in DMC (dimethyl carbonate) for 1 hour, washed, and dried at 80℃ for 4 hours to obtain the positive electrode sheet. The positive electrode sheet is cut into 7cm×7cm pieces to be tested;
[0234] At 60°C, immerse the electrode to be tested in 20 ml of a mixed solution consisting of ethylene carbonate, ethyl methyl carbonate and lithium perchlorate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the molar concentration of lithium perchlorate in the mixed solution is 1 mol / L;
[0235] When the electrode to be tested is immersed in the mixed solution for 48 hours, the hydrogen ion content in the mixed solution is detected, which is recorded as h1 ppm; when the electrode to be tested is immersed in the mixed solution for 72 hours, the hydrogen ion content in the mixed solution is detected again, which is recorded as h2 ppm;
[0236] Calculate the growth rate of hydrogen ion content when the positive electrode is immersed in a mixed solution containing lithium perchlorate h = (h2-h1) / h1×100%; that is, the acidity growth rate.
[0237] The hydrogen ion content (H1, H2) in the mixed solution is detected by the following method:
[0238] Triethylamine and ethyl methyl carbonate (EMC) are prepared into a 0.05 mol / L triethylamine titration solution; the mixed solution in which the positive electrode is immersed is taken as the test solution, 10 to 30 drops of methyl red are added thereto as an indicator, and the triethylamine titration solution is dripped into the test solution containing methyl red, and the amount of triethylamine titration solution is recorded when the test solution turns orange; then the hydrogen ion content is obtained according to the formula:
[0239] Hydrogen ion content = M × V × 20010 / m, the unit of hydrogen ion content is ppm;
[0240] Where: M is the concentration of triethylamine titration solution, unit mol / L,
[0241] V is the volume of titrant consumed by triethylamine, in mL,
[0242] m is the mass of the solution to be tested, in g,
[0243] 20010=20.01×10 3 , 20.01 is the molecular weight of HF. The fully charged positive electrode contains the electrolyte component LiPF6. The positive electrode active material reacts with EC and EMC to dehydrogenate and produce HF in the presence of LiPF6. The amount of HF represents hydrogen ions.
[0244] 400 cycles capacity retention test at 25°C:
[0245] At 25° C., the lithium ion secondary batteries prepared in the examples and comparative examples were subjected to cycle tests according to the following procedures:
[0246] 1) Charge at a constant current of 1C to 4.25V, and charge at a constant voltage until the current is less than 0.05C, repeat this process for more than 3 times, and record the battery capacity C1;
[0247] 2) Charge at 1C constant current to 4.25V, and charge at constant voltage until the current is less than 0.05C.
[0248] 3) Let stand for 5 minutes;
[0249] 4) Discharge at 1C rate to 2.5V;
[0250] 5) Let it sit for 5 minutes.
[0251] Perform cycle testing according to steps 2) to 5) until the lithium-ion secondary battery has been cycled 400 times, and record the capacity C2 of the battery after 400 cycles.
[0252] 25℃ cycle capacity retention rate = C2 / C1×100%.
[0253] DCR growth rate:
[0254] The lithium-ion battery was fixed in capacity, charged to 4.25V at a constant current of 0.33C, then charged to a cut-off current of 0.05C at a constant voltage, discharged at 0.33C to adjust the charge to 50% SOC, left to stand for 2h, and then discharged at 1C at 50% SOC. The initial battery internal resistance was obtained as DCR1;
[0255] The lithium-ion battery was placed in a 25°C constant temperature box, and the lithium-ion battery was discharged at a constant current of 0.33C. Then, the battery was cycled in the constant temperature box at a charge and discharge test rate of 1C / 1C and a cycle voltage range of 2.5-4.25V for a total of 400 cycles.
[0256] After 400 cycles, the battery was discharged at 0.33C to 50% SOC, left to stand for 2 hours, and then discharged at 1C at 50% SOC. The internal resistance of the battery after the cycle was tested to obtain DCR2.
[0257] The battery internal resistance test method is: take the voltage at the last second of static state as V0, the voltage after 18s discharge as V1, the current during discharge as I, DCR=(V0-V1) / I;
[0258] Calculate the DCR growth rate = (DCR2-DCR1) / DCR1×100%.
[0259] It can be seen from the above embodiments that the present invention provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes lithium manganese iron phosphate particles; the molar ratio of manganese element to iron element in the positive electrode active material is a; the acidity growth rate of the positive electrode sheet is h, unit: %; k=b / L, wherein L is the depth of the positive electrode sheet etched by XPS, which is 10nm; k is the peak intensity ratio of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s / nm; b is the peak intensity of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s; a, k and h satisfy the following relationship: a×h / k=8×10 -4 ~10. The positive electrode sheet forms a stable CEI film containing B on the surface of the positive electrode sheet by controlling the manganese-iron ratio, acidity growth rate and peak intensity ratio when etching to a certain depth, preventing manganese ions from dissolving, reducing active lithium consumption and improving the cycle.
[0260] The experimental results show that the battery prepared by the present invention has a capacity retention rate of 60.3-96.4% after 400 cycles at room temperature, and a DCR growth rate of 24.3-56.1% after 400 cycles; while the battery prepared by the comparative example has a capacity retention rate of 45.3-50.4% after 400 cycles at room temperature, and a DCR growth rate of 63-71.5% after 400 cycles. It can be seen that the present invention forms a stable positive electrode solid electrolyte interface film (CEI film) containing boron (B) on the surface of the positive electrode sheet by controlling experimental parameters such as a, k, h, a×h / k, F2-F1, etc., to prevent the dissolution of manganese ions, reduce the consumption of active lithium, and improve the cycle.
[0261] In Examples 3 to 5 of the present application, the values of a×h / k, a, h, and k are all within the preferred range, and the peak intensity difference F2-F1 is also within the preferred range. The obtained battery has a capacity retention rate of 91.5-96.4% after 400 cycles at room temperature, and a DCR growth rate of 24.3-36.0% after 400 cycles. If any of the above values is not within the preferred range, the battery cycle performance will be slightly worse; for example, in Example 8 of the present application, a×h / k is 0.0592, which is within the preferred range of 0.02-3, but the peak intensity difference F2-F1 is 3550, the surface peak intensity is large, and it is not within the preferred range of 0-2000, so the obtained battery cycle performance is slightly worse.
[0262] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes lithium manganese iron phosphate particles; The molar ratio of manganese element to iron element in the positive electrode active material is a; the acidity growth rate of the positive electrode sheet is h, unit: %; When the XPS etching depth is 10 nm, the peak intensity of the B1s peak is F1; when the XPS etching depth is 35 nm, the peak intensity of the B1s peak is F2; The difference between F1 and F2 is greater than 0 and less than or equal to 2000.
2. The positive electrode sheet according to claim 1, characterized in that: k=b / L, where k is the peak intensity ratio of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s / nm; L is the depth of the XPS etching positive electrode sheet, which is 10nm; b is the peak intensity of the B1s peak at the position of 188~192eV in the XPS graph when the positive electrode sheet is subjected to XPS etching analysis, unit: counts / s; The a, k and h satisfy the following relationship: a×h / k=0.0016~9.
8.
3. The positive electrode sheet according to claim 2, characterized in that: a×h / k=0.02~3.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: 0.1≤a≤9。 5. The positive electrode sheet according to claim 4, characterized in that: 0.4≤a≤2.5。 6. The positive electrode sheet according to claim 2, characterized in that: 5≤k≤400。 7. The positive electrode sheet according to claim 6, characterized in that: 9≤k≤108。 8. The positive electrode sheet according to claim 2, characterized in that: The acidity growth rate h is 3~18%.
9. The positive electrode sheet according to claim 8, characterized in that: The acidity growth rate h is 4~16%.
10. The positive electrode sheet according to claim 1, characterized in that: The lithium manganese iron phosphate particles include primary particles, and the average particle size of the primary particles ranges from 50 to 170 nm.
11. A battery, characterized in that: Including positive electrode sheet, negative electrode sheet, separator and electrolyte; The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 10.
12. The battery according to claim 11, characterized in that The electrolyte and / or the positive electrode sheet are provided with a boron-containing compound.
13. The battery according to claim 12, characterized in that The electrolyte includes a boron-containing compound, and the boron-containing compound is selected from one or more of lithium bis(oxalatoborate), tris(trimethylsilyl)borate, lithium difluorooxalatoborate, lithium tetrafluoroborate, tributyl borate and trimethyl borate.
14. An electrical device, characterized in that: A battery comprising any one of claims 11 to 13.
Citation Information
Patent Citations
An electrode material used for a lithium ion secondary battery and a manufacturing method thereof
CN106252658A
Lithium manganese iron phosphate composite material and preparation method thereof, positive electrode material and lithium battery
CN115207332A
Oxide composite positive electrode material coated with borate in situ, preparation method and application
CN116119730A
Phosphorus-position boron-doped nanometer disc-shaped lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN116666624A
Lithium ion battery
CN117497828A
Cited By
Positive electrode sheet, battery, and electric device
WO2026081435A1